Association between vitamins and risk of brain tumors: A systematic review and dose-response meta-analysis of observational studies - Zhang, Weichunbai; Jiang, Jing; He, Yongqi; Li, Xinyi; Yin, Shuo; Chen, Feng; Li, Wenbin (Frontiers in Nutrition, 2022)
Background Brain tumor is one of the important causes of cancer mortality, and the prognosis is poor. Therefore, early prevention of brain tumors is the key to reducing mortality due to brain tumors. Objective This review aims to quantitatively evaluate the association between vitamins and brain tumors by meta-analysis. Methods We searched articles on PubMed, Cochrane Library, Web of Science, and Embase databases from inception to 19 December 2021. According to heterogeneity, the fixed-effects model or random-effects model was selected to obtain the relative risk of the merger. Based on the methods described by Greenland and Longnecker, we explored the dose-response relationship between vitamins and the risk of brain tumors. Subgroup analysis, sensitivity analysis, and publication bias were also used for the analysis. Results The study reviewed 23 articles, including 1,347,426 controls and 6,449 brain tumor patients. This study included vitamin intake and circulating concentration. For intake, it mainly included vitamin A, vitamin B, vitamin C, vitamin E, β-carotene, and folate. For circulating concentrations, it mainly included vitamin E and vitamin D in the serum (25-hydroxyvitamin D and α-tocopherol). For vitamin intake, compared with the lowest intakes, the highest intakes of vitamin C (RR = 0.81, 95%CI:0.66–0.99, I2 = 54.7%, Pfor heterogeneity = 0.007), β-carotene (RR = 0.78, 95%CI:0.66–0.93, I2 = 0, Pfor heterogeneity = 0.460), and folate (RR = 0.66, 95%CI:0.55–0.80, I2 = 0, Pfor heterogeneity = 0.661) significantly reduced the risk of brain tumors. For serum vitamins, compared with the lowest concentrations, the highest concentrations of serum α-tocopherol (RR = 0.61, 95%CI:0.44–0.86, I2 = 0, Pfor heterogeneity = 0.656) significantly reduced the risk of brain tumors. The results of the dose-response relationship showed that increasing the intake of 100 μg folate per day reduced the risk of brain tumors by 7% (P−nonlinearity = 0.534, RR = 0.93, 95%CI:0.90–0.96). Conclusion Our analysis suggests that the intake of vitamin C, β-carotene, and folate can reduce the risk of brain tumors, while high serum α-tocopherol concentration also has a protective effect on brain tumors. Therefore, vitamins may provide new ideas for the prevention of brain tumors. Systematic Review Registration PROSPERO, identifier CRD42022300683.